2017
DOI: 10.1371/journal.pone.0179400
|View full text |Cite
|
Sign up to set email alerts
|

Changes in inflammatory biomarkers in HCV-infected patients undergoing direct acting antiviral-containing regimens with or without interferon

Abstract: Background and aimsIncreased levels of chemokine interferon-gamma (IFN-γ)-inducible protein-10 (CXCL10), soluble CD163 (sCD163) and soluble CD14 (sCD14) have been reported in HCV infection. The aim of this study was to compare, sCD163 and sCD14 levels in HCV-infected patients undergoing direct acting antiviral (DAA)-containing regimens with or without interferon (IFN).MethodssCD163, sCD14 and CXCL10 were longitudinally measured by ELISA in 159 plasma samples from 25 HCV-infected patients undergoing IFN-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 42 publications
(45 reference statements)
10
40
0
1
Order By: Relevance
“…High levels of surrogate microbial translocation markers in HCV patients confirm the observation by other authors who also suggested that microbial translocation may contribute to persistent inflammation and development of fibrosis in chronic HCV infection . Even if the mechanism underlying the link between HCV infection and microbial translocation was beyond the purpose of our study, a possible explanation could be related to gut epithelial damage, as was observed in a study conducted in HIV/HCV coinfected patients, in whom HIV is known to colonise enterocytes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…High levels of surrogate microbial translocation markers in HCV patients confirm the observation by other authors who also suggested that microbial translocation may contribute to persistent inflammation and development of fibrosis in chronic HCV infection . Even if the mechanism underlying the link between HCV infection and microbial translocation was beyond the purpose of our study, a possible explanation could be related to gut epithelial damage, as was observed in a study conducted in HIV/HCV coinfected patients, in whom HIV is known to colonise enterocytes.…”
Section: Discussionsupporting
confidence: 89%
“…The decrease of sCD14 and LBP levels, although not reaching normal values, persisted 3 months after the end of antiviral treatment. Previous studies on the impact of direct‐acting antivirals on systemic immune activation in HCV patients have reported controversial results; while some studies highlighted a reduction of the markers of immune activation during direct‐acting antiviral treatment, others did not find similar changes …”
Section: Discussionmentioning
confidence: 95%
“…Our study also confirms that the production of inflammatory cytokines and chemokines is enhanced in patients with chronic HCV infection and is downregulated by viral eradication . Indeed, antiviral therapy significantly improved IL1‐ra, IL2, IL5, FGF‐basic, GM‐CSF, IFN‐gamma, CCL2, CCL3, CCL4, CCL11, CXCL10, PDGF‐BB, and TNF‐alpha plasma levels.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, this result may be affected by the relatively short follow-up period, as the evaluation of these parameters was performed 1 year after the end of the DAA treatment, and also by the fact that only patients with well-compen- Our study also confirms that the production of inflammatory cytokines and chemokines is enhanced in patients with chronic HCV infection and is downregulated by viral eradication. [28][29][30][31][32][33][34][35][36][37] Indeed, antiviral therapy significantly improved IL1-ra, IL2, IL5, FGF-basic, , faecal calprotectin) before and 1 y after the end of direct-acting antiviral (DAA) treatment. IL: interleukin; ra:receptor agonist; FGF: fibroblast growth factor; G-CSF: granulocyte colony-stimulating factor; GM-CSF: granulocytemacrophage colony-stimulating factor; IFN: interferon; CCL: C-C motif chemokine ligand; CXCL: C-X-C motif chemokine ligand; PDGF: plateletderived growth factor; TNF: tumour necrosis factor GM-CSF, IFN-gamma, CCL2, CCL3, CCL4, CCL11, CXCL10, PDGF-BB, and TNF-alpha plasma levels.…”
Section: P-value (Hcv Post-daa Vs Controls)mentioning
confidence: 99%
“…16,17 In our study, only sCD163 remained significantly elevated in patients that received DAA regimen without RBV. This is in accordance with work by Mascia et al showing sustained high levels of sCD163 in DAA-treated CHC patients, 34 and taken together these findings by us and others suggest that residual macrophage activation plays an important role in residual liver disease despite a general dampening of inflammation.…”
Section: Discussionsupporting
confidence: 93%